Impact of Moderate versus Deep Sedation and Trainee Participation on Adenoma Detection Rate-Analysis of a Veteran Population - Marella, Hemnishil K. (Clin Endosc, 2021)
BACKGROUND/AIMS: The adenoma detection rate (ADR) is used as a quality indicator for screening and surveillance colonoscopy. The study aimed to determine if moderate versus deep sedation affects the outcomes of the ADR and other quality metrics in the veteran population. METHODS: A retrospective review of colonoscopies performed at Memphis Veterans Affairs Medical Center over a one-year period was conducted. A total of 900 colonoscopy reports were reviewed. After exclusion criteria, a total of 229 index, average-risk screening colonoscopies were identified. Data were collected to determine the impact of moderate (benzodiazepine plus opioids) versus deep (propofol) sedation on the ADR, polyp detection rate (PDR), and withdrawal time. RESULTS: Among 229 screening colonoscopies, 103 (44.9%) used moderate sedation while 126 (55%) were done under deep sedation. The ADR and PDR were not significantly different between moderate versus deep sedation at 35.9% vs. 37.3% (p=0.82) and 58.2% vs. 48.4% (p=0.13), respectively. Similarly, there was no significant difference in withdrawal time between moderate and deep sedation (13.4 min vs. 14 min, p=0.56) during screening colonoscopies. CONCLUSIONS: In veterans undergoing index, average-risk screening colonoscopies, the quality metrics of the ADR, PDR, and withdrawal time are not influenced by deep sedation compared with moderate sedation.